Pengaruh Dukungan Sosial Orang Tua terhadap Regulasi Emosi dan Kesejahteraan Psikologis Peserta Didik SMP - Rofiqoh Rov’atul Baroinnisrina; Asieline Wahyu Tri Ardyanti (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Social support from parents plays an important role in the affective development and psychological condition of students. Parental social support plays a crucial role in the affective development and psychological well-being of students. This study aims to examine the extent to which parental social support influences emotional regulation and psychological well-being among junior high school students in Wonoayu District, Sidoarjo. Employing a quantitative correlational method, the research involved 104 students from private junior high schools in the district, selected through purposive sampling. Data were collected using social support, emotional regulation, and psychological well-being instruments and then analyzed using simple linear regression. The results showed that parental social support significantly and positively influenced students' emotional regulation and psychological well-being. A novel discovery in this study is the correlation between parents' educational levels and the quality of support provided to their children. This research underscores the importance of enhancing parental involvement to foster better emotional and psychological outcomes for adolescents.